Grassroots Activism and Representational Politics as Integral to Evangelization a Christian Response - Hrudayaraj, Bala Kiran Kumar (Asian Horizons, 2024)
The 2014 electoral verdict, a significant turning point in India’s political landscape, marked a decline in authoritarian dominance. However, it did not conclusively signify the resolution of the rising authoritarianism in India. The article argues that fostering grassroots political activism and representational politics is not just a political mission but also a constitutive part of the mission of evangelization. Drawing on the insights of Amartya Sen and Catholic social tradition, the article presents a compelling argument for such a political engagement of the Christians in India. Emphasizing Sen’s conceptualization of democracy as public reasoning, wherein citizens engage in rational dialogue and subject their beliefs to critical scrutiny, the article underscores the imperative of informed engagement with critical socio-political issues. Subsequently, it delves into the principle of participation within Catholic social tradition, which advocates for active involvement in socio-political and cultural processes to further the common good. Synthesizing these perspectives, the discourse proffers practical strategies through which the Catholic Church, as a key societal institution, can play a crucial role in cultivating social trust and fortifying the secular fabric of Indian society by fostering grassroots political activism and aiming at representational politics. Such a political engagement is construed as an intrinsic facet of the mission of evangelization.